2005
DOI: 10.1016/j.molcel.2005.02.013
|View full text |Cite
|
Sign up to set email alerts
|

GMP Synthetase Stimulates Histone H2B Deubiquitylation by the Epigenetic Silencer USP7

Abstract: The packaging of eukaryotic genomic DNA into chromatin is modulated through a range of posttranslational histone modifications. Among these, the role of histone ubiquitylation remains poorly understood. Here, we show that the essential Drosophila ubiquitin-specific protease 7 (USP7) contributes to epigenetic silencing of homeotic genes by Polycomb (Pc). We purified USP7 from embryo nuclear extracts as a stable heteromeric complex with guanosine 5'-monophosphate synthetase (GMPS). The USP7-GMPS complex catalyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
238
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(254 citation statements)
references
References 45 publications
15
238
1
Order By: Relevance
“…The histone H3 Lys-9 methyltransferase Setdb1, together with its activating partner, mAM (46), was also identified in the analysis, although the sequence coverage of the corresponding peptides was relatively low, possibly indicating non-stoichiometric amounts or a low abundance complex. Another interesting putative new interactor is the ubiquitin protease encoded by the Usp7 gene, which has been shown in flies to interact genetically with PcG genes (47). These and other new proteins shown in Table I and Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The histone H3 Lys-9 methyltransferase Setdb1, together with its activating partner, mAM (46), was also identified in the analysis, although the sequence coverage of the corresponding peptides was relatively low, possibly indicating non-stoichiometric amounts or a low abundance complex. Another interesting putative new interactor is the ubiquitin protease encoded by the Usp7 gene, which has been shown in flies to interact genetically with PcG genes (47). These and other new proteins shown in Table I and Fig.…”
Section: Resultsmentioning
confidence: 95%
“…[21][22][23][24] However, the ability of exogenous guanosine to fully revert all phenotypes caused by GMPS depletion in vitro (Figure 1) strongly suggests that guanylate biosynthetic function has the most important role in GMPS-dependent maintenance of invasive and tumorigenic phenotypes of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Mammalian GMPS has been the subject of several studies addressing its unconventional (GMP-unrelated) roles in the regulation of activity of ubiquitin-specific protease 7 (USP7). [21][22][23][24] However, because of the newly revealed importance of guanylate metabolism in control of melanoma cell invasion and tumorigenicity, 8 GMPS emerges as an attractive target for anti-cancer therapy.…”
mentioning
confidence: 99%
“…Two molecular mechanisms, which are not mutually exclusive, have been described that can regulate USP7 activity: interaction with specific proteins and PTM. Studies in D. melanogaster and human cells found the metabolic enzyme GMP synthase to stimulate the ability of USP7 to deubiquitinate histone H2B [30][31][32] , whereas the TSPYL5 protein can inhibit the activity of USP7 towards p53 in mammalian cells 33 . Besides these two proteins, Sowa et al 34 identified 430 additional USP7-interacting proteins using a global proteomic analysis.…”
Section: Discussionmentioning
confidence: 99%